Predictors of excess fluid volume in hemodialysis patients: an observational study - Maria Isabel da Conceição Dias Fernandes; Jéssica Dantas de Sá Tinôco; Renata Marinho Fernandes; Juliana Barbosa da Silva; Anna Thays Dias Almeida; Cecília Maria Farias de Queiroz Frazão; Marcos Venícius de Oliveira Lopes; Ana Luisa Brandão de Carvalho Lira (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to assess risk factors for excess fluid volume in hemodialysis patients. Methods: a retrospective case-control study was conducted. A total of 392 patients (196 cases and 196 controls) from two hemodialysis centers were included. Sociodemographic data and 23 risk factors for excess fluid volume were assessed using a data collection form. Data were analyzed using a multivariate logistic regression model. Results: the insufficient knowledge (OR=2.06), excessive fluid intake (OR=2.33), inadequate fluid removal during hemodialysis (OR=2.62) and excessive sodium intake (OR=1.91) risk factors may increase the chance of occurrence of excess fluid volume in hemodialysis patients by approximately two times. Education level (OR=0.95) and age (OR=0.97) are protective factors for excessive fluid volume. Conclusions: knowing these risk factors may help nurses with accurate and rapid diagnostic inference of the risk of excessive fluid volume.